Ceremonialul lecturii. Note marginale efectuate de principii români - Mihaela Necula (Revista de Istorie și Teorie Literară)
The article is about the marginal notes on manuscripts and old books dating from the 15th to 19th century copied under the royal patronage or ordered by a prince or by the members of the royal family of the Romanian lands. There are manuscripts with various subjects that shows the involvement of principles in the evolution of old book and old literature. These marginal notes give a perspective on the ceremony of reading. The passion of reading of this type of literature is also found at Constantin Brâncoveanu, Ştefan Voievod, Bogdan Voievod, Ioan Ieremia Movilă, Matei Basarab, Constantin Mavrocordat and other Romanian princes. They often consulted astrologer´s predictions, read the calendars for the political character, gave the books for writing and sometimes they were teaching their children through them.